Pax7 is Required for Muscle Satellite Cell Specification and Regenerative Myogenesis - Seale, Patrick (My University, 2003)
Muscle satellite cells are a distinct population of myogenic progenitors that mediate the postnatal growth and regeneration of skeletal muscle. To gain insight into the genetic regulation of satellite cell function during muscle regeneration, genes expressed specifically in these cells were identified by representational difference analysis of cDNAs. Notably, the paired-box transcription factor Pax7 was isolated as a gene specifically expressed in quiescent and activated satellite cells. Cell culture and histological analysis of Pax7-deficient muscle revealed a complete absence of satellite cells. This result demonstrates a requirement for Pax7 upstream of MyoD and Myf5 in the specification of muscle satellite cells. Consistent with their lack of satellite cells, adult Pax7 mice displayed an aggravated muscle wasting phenotype characterized by spinal kyphosis and reduced muscle mass. Acute muscle damage led to extensive calcification and deposition of adipose and fibrotic tissues with the appearance of rare regenerated myofibers. Importantly, analysis of Pax7 muscle suspensions indicated that myogenic cells expressing Pax3 and MyoD were responsible for this low level of regeneration.
To characterize the role of adult stem cells in skeletal muscle, we investigated the myogenic potential of muscle-derived CD45+:Scal+ cells in vivo during regeneration and in vitro using coculture assays. CD45+ and Scal+ cells isolated from uninjured muscle were uniformly non-myogenic. Strikingly, 7-10% of CD45+:Scal+ cells purified from regenerating muscle activated the myogenic program by a Pax7-dependent mechanism in response to activation of the Wnt signaling pathway. Furthermore, expression of Pax7 was sufficient to induce myogenic commitment in CD45+:Scal+ cells from uninjured muscle. This result demonstrates that non-satellite cell derived myogenic progenitors possess a physiological role in muscle regeneration and tissue homeostasis.
Taken together, this work establishes a requirement for Pax7 in the specification of muscle satellite cells and for the myogenic recruitment of adult stem cells populations during tissue repair. Importantly, these studies also suggest that targeted therapies to activate Wnt signaling and Pax7 expression in adult stem cells will be effective for promoting muscle regeneration in patients with degenerative neuromuscular diseases or muscular dystrophies.
Keywords: Biology; Biology